Cyberpsychology and the Brain: The Interaction of Neuroscience and Affective Computing - Thomas D. Parsons (Cambridge University Press, 2017)
Cyberpsychology is a relatively new discipline that is growing at an alarming rate. While a number of cyberpsychology-related journals and books have emerged, none directly address the neuroscience behind it. This book proposes a framework for integrating neuroscience and cyberpsychology for the study of social, cognitive, and affective processes, and the neural systems that support them. A brain-based cyberpsychology can be understood as a branch of psychology that studies the neurocognitive, affective, and social aspects of humans interacting with technology, as well as the affective computing aspects of humans interacting with computational devices or systems. As such, a cyberpsychologist working from a brain-based cyberpsychological framework studies both the ways in which persons make use of devices and the neurocognitive processes, motivations, intentions, behavioural outcomes, and effects of online and offline uses of technology. Cyberpsychology and the Brain brings researchers into the vanguard of cyberpsychology and brain research.